Pulmonary metastasectomy for esophageal basaloid squamous cell carcinoma component at 66 months after esophagectomy - Kumiko Sekiguchi; Takeshi Matsutani; Tsutomu Nomura; Nobutoshi Hagiwara; Akihisa Matsuda; Hidetsugu Hanawa; Keisuke Mishima; Nobuhiko Taniai; Ryuji Ohashi; Hiroshi Yoshida (Surgical Case Reports, 2020)
Abstract Background Solitary pulmonary metastasis from esophageal basaloid squamous cell carcinoma (BSCC) components is an extremely rare recurrence of esophageal squamous cell carcinoma (SCC). Case presentation A 68-year-old Japanese woman was found to have a suspected malignant mass, approximately 2 cm in diameter, in her left lower pulmonary lobe, at 66 months after undergoing a curative esophagectomy with three-field lymph node dissection for esophageal SCC with a focal basaloid component. After a CT-guided biopsy, pathological examination indicated a metastasis from esophageal BSCC components. She underwent a thoracoscopic partial resection of the left lower pulmonary lobe for the solitary pulmonary metastasis. The pathohistology of the resected specimen led to diagnosis of metastatic esophageal BSCC, which showed immunohistochemical findings similar to those of the primary esophageal carcinoma. The patient received two courses of adjuvant chemotherapy (5-fluorouracil, docetaxel plus nedaplatin) and recovered to resume a normal life with maintenance therapy. However, multiple lung and brain metastases were diagnosed at 2 years after the pulmonary metastasectomy. She survived 5 years and 6 months after the pulmonary metastasectomy, but died at 10 years and 6 months after her initial esophagectomy. Conclusion This was a rare surgical resected case of solitary pulmonary metastasis from esophageal BSCC components.